A Flora mistica brasileira, design editorial e ilustração: o projeto gráfico de um compêndio experimental ilustrado - Silva, Renan Neves (2020)
Brazilian culture is a fruit of a large miscigenation process, found in the sum and ressignification of tradition inherited from native indigenous and from the people originating from different continents, as Africa and Europe, the way to form its own identity. One of these inherited traditions from this cultural intersection is the mystical use of plant species, since colonial Brazil and up to today, are found records about the practice in the country. Today, this inherited culture is related to traditional communities the way these people relate with their environment, however, capitalist system’s development endengers the traditional knowledge’s perpetuation when changing the relation these communities’ relation with the land. The current study then intends to change the designer’s look to the brazilian narrative, as a way to generate visibility to a big potential cultural representative theme and that is endegered. In this context, it tries to understand how design will be able to serve as a useful tool to the recognition about the brazilian mystical use of plant species, for this reason, it will also be used Ethodesign as a research tool able to assist in the understanding of the cultural practice, the illustration as a representation source and the Editorial Design as a way of materialization. This, bearing in mind the cultural that involves the mystical Brazilian flora, being expected this paper contributes generating more visibility to the theme, stimulating this discussion in the society and also encouraging design productions with national references beyond stereotypes linked to Brazil.